Liberalizing climate-friendly goods and technologies in the WTO: product coverage, modalities, challenges and the way forward - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2010)
The Doha Round Agenda (paragraph 31(3)) mandates to liberalize environmental goods and services. This mandate offers a good opportunity to put climate-friendly goods and services on a fast track to liberalization. Agreement on this paragraph should represent one immediate contribution that the WTO can make to fight against climate change. This paper presents the key issues surrounding liberalized trade in climate-friendly goods and technologies in WTO environmental goods negotiations. It begins with what products to liberalize and how. Clearly, WTO environmental goods negotiations to date show that WTO member countries are divided by this key issue. Focusing on the issue, the paper explores options available to liberalize trade in climate-friendly goods and technologies, both within and outside the WTO, and along with these discussions, discusses how to serve the best interests of developing countries.
Keywords: F18; F13; Q56; Q54; Q58; Q48; 330; Environmental Goods and Services; Low-Carbon Goods and Technologies; Doha Round; WTO